Development of equatorial delta-front patch reefs during the Neogene, Borneo - Wilson, Moyra (SEPM - Soc Sedimentary Geology, 2005)
Miocene patch reefs formed in turbid waters associatedwith high siliciclastic input at the seaward margin of the equatorial Mahakam Delta in eastern Borneo, SE Asia. Patch reefs were initiated on unstable substrates on localized low-relief bathymetric highs associated with delta-front channels or distributary mouthbars in the process of abandonment. Patch reefs developed only in shallow waters, formed low-relief buildups, lacked rigid frameworks, and had gently sloping margins. Although the biodiversity of the patch reefs may be comparable with that of clear-water systems, all the organisms present were adapted to turbid-water areas associated with siliciclastic, and sometimes nutrient, influx. The patch reefs were transient features, and their demise was influenced by increased siliciclastic and nutrient input, perhaps at times associated with deepening. Carbonate production and bioherm or patch-reef development can occur in turbid-water delta-front areas as localized or more regionally extensive units during any phases of eustatic sea level.However, development and preservation of turbid-water carbonates is most likely during relative transgression or perhaps late lowstand periods. This is in contrast with common highstand carbonates from clear-water shelves, where nearly pure carbonates interdigitate with siliciclastics. It is the interplay between factors such as tectonics, eustasy, delta lobe switching, shelf currents, and amount and size fraction of siliciclastic influx that ultimately controlled carbonate development and preservation.